Toben Lewo: Social Safety Nets Within The Framework of Religious Moderation - Anselmus Dore Woho Atasoge; Maria Yulita C. Age; Primiaty Natalia Sabu Kopong (Fakultas Teologi, Universitas Sanata Dharma, 2024)
By conducting the toben lewo ritual, the religious community in Botung village organizes, interprets, and reconstructs their lives within the framework of achieving collective salvation. Salvation is manifested in socio-religious harmony, which is also an implication of the mainstreaming of religious moderation in Indonesia. This study elaborates on three main questions. First, how is the toben lewo ritual conducted? Second, how do the people of Botung village interpret this ritual? Third, what are the implications in promoting religious moderation in Indonesia? A qualitative method was selected with the aim of exploring the knowledge, experiences, opinions, and feelings of informants regarding the toben lewo ritual as a social salvation system in the context of religious moderation. The study was conducted in Botung village, Adonara Island, East Flores Regency. The techniques of data collection were observation, interviews, and document studies. The data collection was collected from September 2021 to May 2023. Primary data was obtained by conducting structured interviews with ritual participants and the representation of women and youth. The secondary data were from previous studies and documentary photographs. The findings revealed that by carrying out the toben lewo ritual, the village will be freed from guilt as the cause of disasters and calamities, which disrupt its relationship with the divine, ancestors, humans, and the universe. The ritual serves to restore and mend these three-dimensional relationships. The ritual brings forth and affirms harmony with the divine, ancestors, people, and the universe. This study can serve as a gateway to promote the idealism of religious moderation in Indonesia and enrich the knowledge in the fields of sociology and anthropology.